Participatory management of community-based tourism: A network perspective. Issue 4 (8th August 2017) - Burgos, Andrés; Mertens, Frédéric
Abstract: Community-based tourism (CBT) aims to promote community development by combining income generation, social inclusion, gender equity, and environmental sustainability. In CBT projects, different sociocultural community groups with distinct roles, concerns, and priorities need to collaborate to manage tourism activities. However, little is known about how management and development outcomes of CBT are associated with patterns of collaboration among community groups. We applied social network analysis to map the collaboration network among individuals involved in tourism activities ( n = 124) in a coastal community in Brazil. Community groups were defined by gender, age, birthplace, education level, participation in tourism associations, income-generating activity, tourism occupation, and years of experience in CBT. The network was highly connected, while the collaboration patterns among groups exhibit a modular structure with features of both horizontality and leadership. We discuss how this balanced collaborative structure can contribute to community development in accordance with the core principles of CBT.